The Acute Effects of Swimming on Appetite, Food Intake, and Plasma Acylated Ghrelin - James A. King; Lucy K. Wasse; David J. Stensel (Hindawi Limited, 2011)
Swimming may stimulate appetite and food intake but empirical data are lacking. This study examined appetite, food intake, and plasma acylated ghrelin responses to swimming. Fourteen healthy males completed a swimming trial and a control trial in a random order. Sixty min after breakfast participants swam for 60 min and then rested for six hours. Participants rested throughout the control trial. During trials appetite was measured at 30 min intervals and acylated ghrelin was assessed periodically (0, 1, 2, 3, 4, 6, and 7.5 h. 𝑁=10). Appetite was suppressed during exercise before increasing in the hours after. Acylated ghrelin was suppressed during exercise. Swimming did not alter energy or macronutrient intake assessed at buffet meals (total trial energy intake: control 9161 kJ, swimming 9749 kJ). These findings suggest that swimming stimulates appetite but indicate that acylated ghrelin and food intake are resistant to change in the hours afterwards.